Living in Tier 2: educators' perceptions of MTSS in urban schools. Issue 10 (23rd August 2020) - Braun, Gina; Kumm, Skip; Brown, Christerralyn; Walte, Samantha; Hughes, Marie Tejero; Maggin, Daniel M.
ABSTRACT: Despite multi-tiered systems of support (MTSS) being implemented for over a decade in the United States, practitioners are continuously challenged with implementing the framework to meet the needs of their students. This qualitative study aimed to examine the perspectives of educators in high-need urban schools regarding the implementation of academic MTSS. Nineteen educators were interviewed. The interviews were analyzed to identify teachers' understanding of the MTSS process, tiered interventions, and their experiences with MTSS. Two major themes emerged: (a) due to frequent changes in school-wide MTSS, educators felt confused about the process and (b) educators thought Tier 2 interventions were effective for students needing limited assistance, but schools struggle to intensify interventions for non-responders. Further research is needed regarding the use of evidence-based practices in high-need urban settings.